2020
DOI: 10.1007/s11252-020-00929-z
|View full text |Cite
|
Sign up to set email alerts
|

Where the wild things are! Do urban green spaces with greater avian biodiversity promote more positive emotions in humans?

Abstract: Urban green space can help mitigate the negative impacts of urban living and provide positive effects on citizens' mood, health and well-being. Questions remain, however, as to whether all types of green space are equally beneficial, and if not, what landscape forms or key features optimise the desired benefits. For example, it has been cited that urban landscapes rich in wildlife (high biodiversity) may promote more positive emotions and enhance well-being. This research utilised a mobile phone App, employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 107 publications
5
71
0
Order By: Relevance
“…This can also be useful in urban environments, where knowledge can help mitigate conflicts related to urban green infrastructure. However, future research should aim to discriminate preferences between different vegetative life forms (i.e., grasslands, shrubs, or trees), as recent studies have shown that spatial heterogeneity of urban green areas may be related to psychological response [20]. Therefore, assessing this relationship is crucial to better understand the case of Chile, since most of the urban parks of the metropolitan area are of the "Savanna type": a simple structure with grass and isolated trees.…”
Section: Discussionmentioning
confidence: 99%
“…This can also be useful in urban environments, where knowledge can help mitigate conflicts related to urban green infrastructure. However, future research should aim to discriminate preferences between different vegetative life forms (i.e., grasslands, shrubs, or trees), as recent studies have shown that spatial heterogeneity of urban green areas may be related to psychological response [20]. Therefore, assessing this relationship is crucial to better understand the case of Chile, since most of the urban parks of the metropolitan area are of the "Savanna type": a simple structure with grass and isolated trees.…”
Section: Discussionmentioning
confidence: 99%
“…When data on actual biodiversity are not available, a proxy measure may be used (Cameron et al, 2020). The proxy measure, perceived biodiversity, is a person's subjective assessment of the biodiversity that they think is present in an environment (Fuller et al, 2007;Dallimer et al, 2012).…”
Section: Fig 2 Measurement Of Actual and Perceived Biodiversitymentioning
confidence: 99%
“…Perceived biodiversity is measured by asking people for their individual assessment of the species identity or richness in an environment through self-report questionnaires (Fuller et al, 2007;Dallimer et al, 2012;Marselle et al, 2016;Southon et al, 2018;Cameron et al, 2020). Perceived biodiversity has stronger correlations with well-being than actual biodiversity (Dallimer et al, 2012;Cameron et al, 2020;Meyer-Grandbastien et al, 2020). However, the proxy measure of perceived biodiversity cannot replace a measure of actual biodiversity (Hoyle, 2020).…”
Section: Fig 2 Measurement Of Actual and Perceived Biodiversitymentioning
confidence: 99%
See 2 more Smart Citations